Effects of 6 weeks of watermelon juice supplementation on total antioxidant capacity and VO2max in elite taekwondo athletes - Aghabeigi Amin, P.; Azizi, M.; Tahmasebi, W. (European Journal of Applied Physiology, 2025)
Introduction and objective The natural product watermelon contains a high concentration of antioxidants that have the potential to mitigate the oxidative damage resulting from the generation of free radicals` post-exercise. As such, this study aims to explore the impact of 6 weeks of watermelon juice supplementation on the antioxidant capacity and vo2max of elite female taekwondo athletes.